PENGARUH PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP PENINGKATAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PAI-BP DI KELAS XI MIPA 2SMAN 1 BENAI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Rika Yulianti; Sarmidin Sarmidin; Alhairi Alhairi (Universitas Islam Kuantan Singingi, 2023)
This study aims to determine the effect of the implementation of the Project Based Learning Model on increasing student interest in the PAI-BP Subject of Class XI MIPA 2 at SMA Negeri 1 Benai, Benai District, Kuantan Singingi Regency. Based on the results of data collection by means of observation, questionnaires, interviews and documentation, then analyzed the data using the Simple Linear Analysis formula and using SPSS 21.0 data, it can be concluded that: PAI and BP lessons in Class XI MIPA 2 at SMA Negeri 1 Benai, Benai District, Kuantan Singingi Regency are according to the value of the coefficient of determination (R square) of 0.014 (is the square of the correlation coefficient, or 0.119 x 0.119 = 0.014161). The magnitude of the coefficient of determination (R square) of 0.014 is equal to 1.4%, this number means that the application of the Project Based Learning learning model in Islamic Religious Education and Character Education subjects has an effect on the learning motivation of students in class XI MIPA 2 by 1.4%. While the rest is influenced by other variables.